2019
DOI: 10.1108/sampj-11-2018-0302
|View full text |Cite
|
Sign up to set email alerts
|

Countries’ regulatory context and voluntary carbon disclosures

Abstract: Purpose This study aims to analyse the relationship between countries’ regulatory context and voluntary carbon disclosures. To date, little attention has been paid to how specific climate change-related regulation influences companies’ climate change disclosures, especially voluntary carbon reporting. Design/methodology/approach The New Institutional Sociology perspective has been adopted to examine the pressure of a country’s climate change regulation on voluntary carbon reporting. This research uses Tobit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 80 publications
3
25
0
Order By: Relevance
“…The results of the Regulative variable are consistent with previous studies (Freedman & Jaggi, 2005; Jira & Toffel, 2013; Luo et al, 2012), despite being focused on generic environmental regulations. This result is also consistent with the findings of Mateo‐Márquez et al (2020), who concluded that regulative pressures related to climate change positively influence voluntary carbon disclosures. However, they examined the response decision and the level of disclosure together using a tobit model, thus making it difficult to disaggregate the effect of regulative pressures on firms' decisions to voluntarily disclose carbon data.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the Regulative variable are consistent with previous studies (Freedman & Jaggi, 2005; Jira & Toffel, 2013; Luo et al, 2012), despite being focused on generic environmental regulations. This result is also consistent with the findings of Mateo‐Márquez et al (2020), who concluded that regulative pressures related to climate change positively influence voluntary carbon disclosures. However, they examined the response decision and the level of disclosure together using a tobit model, thus making it difficult to disaggregate the effect of regulative pressures on firms' decisions to voluntarily disclose carbon data.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this study provides evidence against analyzing companies' decisions to voluntarily disclose carbon information and the quality of their disclosures together. This is in contrast to the prior literature on voluntary carbon disclosure that uses a tobit model in order to explain both aspects (e.g., González‐González & Zamora‐Ramírez, 2016b; Guenther, Guenther, Schiemann, & Weber, 2016; Mateo‐Márquez et al, 2020).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although there has been considerable research into the factors influencing voluntary carbon disclosure, there is still very little scientific understanding of the institutional pressures involved, especially those related to the regulative dimension. In this regard, previous studies have found that the regulative context plays a crucial role in influencing voluntary carbon disclosure on the part of companies [6,7]. Prior investigation has found that climate-related laws contribute to increased visibility of climate change challenges in society.…”
Section: Introductionmentioning
confidence: 98%